True familial aggregation of recurrent furunculosis in families from the Province of Villa Clara - Vicente José Hernández Moreno; Manuela Herrera Martínez (Acta Médica del Centro)
Introduction: recurrent furunculosis consists of the sequential appearance of several boils in the patient over a period of months or years. Most cases are attributable to Staphylococcus aureus. Objective: to identify genetic susceptibility in individuals affected by recurrent furunculosis according to the true familial aggregation of the disease in a group of families with affected individuals. Methods: through an analytical study of a cross-sectional cohort reconstructed through a family strategy design, the information obtained from 132 patients aged three to 74 years and 43 healthy adults with no personal history of furunculosis in five municipalities of the Province of Villa Clara was analyzed. 2019 and 2022. Family aggregation was established using two different criteria. The variables were analyzed in accordance with their nature and the objectives of the study. Results: true family aggregation was identified for both criteria, both for all relatives and for specific degrees of relationship, as well as the risk of furunculosis possessed by blood relatives of sick people. Conclusions: the existence of other family members with the disease underlies the susceptibility to recurrent furunculosis in the individuals studied.